Design de produção na narrativa transmídia: recomendações para projeto visual em múltiplos suportes midiáticos - KURZ, Lucas de Moura (2018)
The transmedia culture, significant and recurring in the present scenario, provides complex opportunities to create increasingly immersive work. Concurrently, and as a result, it requires a new Design approach, considering the new challenge of designing an experience through various media so that it is connected and is perceived as a whole. One of the elements that directly interfere in the way the various parts of a transmedia narrative may be connected is the visual aspect conceived in Production Design. This research aimed to understand the principles of Production Design applied to the processes of elaboration of a transmedia narrative, aiming to propose recommendations for processes of creation of transmedia storytelling in the perspective of Production Design. In this exploratory study, when mapping the concepts and techniques in Design, Production Design and transmedia storytelling, it was possible to create a set of thirteen recommendations for visual project on multiple media.